Analysis and Modeling of Particle Velocities in Premixed Abrasive Water Jets. (25th October 2020) - Zuo, Weiqin; Huang, Cheng; Liu, Yanwei; Han, Hongkai; Hao, Fuchang; Zhao, Fajun; Huang, Fei
Abstract : The premixed abrasive jet possesses a strong strike ability and is widely used in oil and gas exploitation, machining, rust removal, and other fields. The superstrong, forceful impact of the premixed abrasive jet is mainly provided by high-speed abrasive groups. Hence, the abrasive velocity is the basis of this research, by applying the distribution law of abrasive impact force. In this paper, the particle velocity of the premixed abrasive jet is analyzed theoretically, and the corresponding particle velocity model is established. The real-time contrast interpolation method is employed to solve the problem of the variable drag coefficient. Factors such as the nozzle structure, average abrasive diameter, abrasive density, and jet flow are utilized to determine the abrasive velocity of the nozzle outlet. The numerical solution for the abrasive velocity is obtained by dividing the high-pressure pipe and nozzle into several sections, along the axis. Finally, the calculated particle velocity is compared with the particle image velocity measurement (PIV), to verify the correctness of the established model. These results demonstrate that the model calculation is in effective agreement with the experimental results. The deviation between the theoretical value and the experimental mean is 0.18 m/s. The standard deviation of the experimental results is 3.81-4.22 m/s, while the average error is less than 4%.